2023
DOI: 10.3390/jof9020181
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adaptation Has Resulted in Aggressiveness Variation of Calonectria pseudonaviculata on Hosts Buxus, Pachysandra, and Sarcococca

Abstract: Calonectria pseudonaviculata (Cps) infects Buxus (boxwood), Pachysandra (pachysandra), and Sarcococca spp. (sweet box); yet, how it adapts to its hosts has been unclear. Here, we performed serial passage experiments with the three hosts and measured Cps changes in three aggressiveness components: infectibility, lesion size, and conidial production. The detached leaves of individual hosts were inoculated with isolates (P0) from the originating host, followed by nine serial inoculations of new leaves of the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The mould was suspended in 15 µL sterile distilled water then transferred onto a glass slide for microscopy. Following observations of rod‐shaped conidia, typical of Calonectria spp., 1‐µL drops of the suspensions were pipetted from slides onto acidified potato dextrose agar (PDA) for isolation (Kong et al., 2023). Clean colonies were only obtained from the Madrid and Sainte‐Foy‐la‐Grande samples (Figure 3) and were subcultured on regular PDA.…”
Section: Figurementioning
confidence: 99%
“…The mould was suspended in 15 µL sterile distilled water then transferred onto a glass slide for microscopy. Following observations of rod‐shaped conidia, typical of Calonectria spp., 1‐µL drops of the suspensions were pipetted from slides onto acidified potato dextrose agar (PDA) for isolation (Kong et al., 2023). Clean colonies were only obtained from the Madrid and Sainte‐Foy‐la‐Grande samples (Figure 3) and were subcultured on regular PDA.…”
Section: Figurementioning
confidence: 99%
“…However, the mechanism of this pathogen's adaptation to different host plants has been undefined until recently. Kong et al [9] conducted a series of experiments to understand the adaptation process of Cps to its hosts, by measuring three components of aggressiveness: infectibility, lesion size, and conidial production.…”
mentioning
confidence: 99%
“…The results indicated that all boxwood isolates maintained their capability of infection and lesion expansion through the ten passages, whereas most non-boxwood isolates lost these abilities during the passages. Isolates from plants of origin (-P0), and their descendants isolated from passages 5 (-P5) and 10 (*-P10), were used to evaluate changes in aggressiveness toward all three hosts with cross-inoculation [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation